Photodegradation of dipyrone by heterogeneous catalysis using TiO2/UV (Research, Society and Development, 2020)
The main goal of the water and wastewater treatment plants is to remove the organic load. The removal of other types of compounds, such as the emerging contaminants, usually found in trace order concentrations (µg L-1 to ng L-1) is not efficient. Thus, new treatment alternatives are being investigated and, therefore, the proposed work aimed to evaluate the removal of sodium dipyrone in aqueous medium, through the heterogeneous photocatalysis process, using titanium dioxide (TiO2) as a semiconductor, employing radiation. artificial and / or solar ultraviolet, monitored by UV-Visible spectroscopy. The degradation study was performed using two different water sources (ultrapure and river water). The sodium dipyrone concentration was monitored using UV-Visible spectrometer at 258 nm  of wavelength. The results indicated that using 75 mg L-1 TiO2/UV process, 80% of the sodium dipyrone (20 mg L-1) was removed after 60 minutes of irradiation. The TiO2/solar UV radiation was also efficient, removing 70% of the drug after 60 minutes of treatment. By using river water as the contaminated medium, 80% and 54% of dipyrone was removed using artificial and solar UV, respectively. Total organic carbon (TOC) analysis showed that approximately 30% of sodium dipyrone was mineralized in the same time period (60 min). The total mineralization od dipyrone was not observed probably due to the generation of degradation, which were not the main objective of study in the present work.